2016
DOI: 10.1104/pp.16.01443
|View full text |Cite
|
Sign up to set email alerts
|

Defense Responses in Aspen with Altered Pectin Methylesterase Activity Reveal the Hormonal Inducers of Tyloses

Abstract: (E.J.M.). Tyloses are ingrowths of parenchyma cells into the lumen of embolized xylem vessels, thereby protecting the remaining xylem from pathogens. They are found in heartwood, sapwood, and in abscission zones and can be induced by various stresses, but their molecular triggers are unknown. Here, we report that down-regulation of PECTIN METHYLESTERASE1 (PtxtPME1) in aspen (Populus tremula 3 tremuloides) triggers the formation of tyloses and activation of oxidative stress. We tested whether any of the oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 64 publications
(104 reference statements)
1
24
0
Order By: Relevance
“…Our study also described the formation of previously reported space-filling parenchyma cells (Lu et al, 1991;Niki et al, 1998;Pegg et al, 2018) during periods of prolonged flooding stress that cosmetically resemble tyloses found in hardwood plants (Esau, 1965;Carlquist, 2013;Leśniewska et al, 2017). The biological significance of these "tylose-like cells" (TLCs) forming in Pisum and Cicer samples is unclear with respect to formation and eventual filling of aerenchyma cavities during periods of flooding stress.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Our study also described the formation of previously reported space-filling parenchyma cells (Lu et al, 1991;Niki et al, 1998;Pegg et al, 2018) during periods of prolonged flooding stress that cosmetically resemble tyloses found in hardwood plants (Esau, 1965;Carlquist, 2013;Leśniewska et al, 2017). The biological significance of these "tylose-like cells" (TLCs) forming in Pisum and Cicer samples is unclear with respect to formation and eventual filling of aerenchyma cavities during periods of flooding stress.…”
Section: Discussionsupporting
confidence: 57%
“…Consistent with previous reports (Lu et al, 1991;Niki et al, 1998) aerenchyma became partly occluded with new tissue expanding from the margin of the vascular cavity within 24-48 h of flooding (Figures 1B, C, J and 2C, D). We described these tissues as being composed of large, nucleated "bubble-like" cells that we name "tylose-like cells" (TLCs) due to their cosmetic resemblance to tyloses found in xylem vessels of various hardwoods (Esau, 1965;Carlquist, 2013;Leśniewska et al, 2017). Interestingly, toluidine blue stained tissue near the margins of the aerenchyma and the TLCs a bright magenta color that was not found elsewhere in the root cross section ( Figures 1B, C).…”
Section: Distinct Morphological Characteristics Accompany Aerenchyma mentioning
confidence: 99%
“…Trauma induced gels have a high abundance of antimicrobial SMs from different chemical pathways including catechol, flavonoids and coumarins (Rioux et al, 1998;Del Rio et al, 2001;Baum and Schwarze, 2002), indicating that a different secondary metabolic pathway is possibly triggered in vessel-associated cells in response to pathogenesis (Wallis and Truter, 1978). A recent study by Lesniewska et al (2017) revealed that down regulation of Pectin Methlesterase1 (PtxtPME1) via jasmonates (i.e. jasmonic acid and metyl jasmonate) A c c e p t e d M a n u s c r i p t mediated ethylene signaling, when working in synergy with 1-aminocyclopropane-1carboxylic acid (ACC), trigger gel and tylosis development in aspen plantlets.…”
Section: Reaction Zones Tyloses and Gelsmentioning
confidence: 99%
“…Jasmonates have previously been connected to secondary growth in A. thaliana (Sehr et al, 2010 ). Also, treatment with jasmonates to aspen plantlets induced the formation of tyloses, which are occlusions of xylem vessels that serve as a barrier against pathogens (Leśniewska et al, 2017 ). This study also showed that combined exogenous application of ACC and jasmonic acid triggered tyloses formation in an ethylene signaling-dependent manner.…”
Section: Resultsmentioning
confidence: 99%